Fusarium paranaense sp. nov., a member of the Fusarium solani species complex causes root rot on soybean in Brazil. Issue 1 (January 2016) - Costa, Sarah S.; Matos, Kedma S.; Tessmann, Dauri J.; Seixas, Claudine D.S.; Pfenning, Ludwig H.
Abstract: Isolates of Fusarium obtained from soybean plants showing symptoms of root rot collected in subtropical southern and tropical central Brazil were characterized based on phylogenetic analyses, sexual crossing, morphology, and pathogenicity tests. A novel species within the Fusarium solani species complex (FSSC) causing soybean root rot is formally described herein as Fusarium paranaense . This species can be distinguished from the other soybean root rot pathogens in the FSSC, which are commonly associated with soybean sudden death syndrome (SDS) based on analyses of the combined DNA sequences of translation elongation factor 1-α and the second largest subunit of RNA polymerase II and on interspecies mating compatibility. Bayesian and maximum parsimony phylogenetic analyses showed that isolates of F. paranaense formed a distinct group in clade 3 of the FSSC in contrast to the pathogens currently known to cause SDS, which are in clade 2. Female fertile tester strains were developed that can be used for the identification of this new species in the FSSC based on sexual crosses. All isolates were heterothallic and belonged to a distinct mating population. Fusarium tucumaniae, a known SDS pathogen, was found in the subtropical southern region of the country.